2012
DOI: 10.1063/1.4766181
|View full text |Cite
|
Sign up to set email alerts
|

Structural incommensurate modulation rule in hexagonal Ba(Ti1-xMx)O3-δ (M = Mn, Fe) multiferroics

Abstract: The structural incommensurate modulation (SIM) rule in hexagonal Ba(Ti1-xMx)O3-δ (1/18 ≤ x ≤ 1/3, M = Mn, Fe) multiferroic ceramics is investigated using transmission electron microscope (TEM). Our systematic analysis on the modulation characteristics in the electron diffraction patterns, especially along [001] direction, reveals that three types of anti-phase domain boundaries (APBs) dominate the SIMs. According to the derived APB models, the calculated oxygen vacancies at both O1 (face sharing) and O2 (corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In spite that the concentration of Ti 3þ ions and Vo in the PA samples cannot be obtained by fitting their susceptibilities using the CW formula, our systematic analysis on the electron diffraction patterns provides us an averaged Vo distribution at O1 and O2 sites from the corresponding APB structures. 18 In the AG BTM11 and AG BTM17, the vacancy contents d ¼ 0.141 and 0.189 are consistent with our calculation based on the CW fitting. In the PA BTM11 and PA BTM17, the vacancy contents are d ¼ 0.097 and 0.103, respectively, which are consistent with our XRD refinements.…”
Section: -supporting
confidence: 88%
See 2 more Smart Citations
“…In spite that the concentration of Ti 3þ ions and Vo in the PA samples cannot be obtained by fitting their susceptibilities using the CW formula, our systematic analysis on the electron diffraction patterns provides us an averaged Vo distribution at O1 and O2 sites from the corresponding APB structures. 18 In the AG BTM11 and AG BTM17, the vacancy contents d ¼ 0.141 and 0.189 are consistent with our calculation based on the CW fitting. In the PA BTM11 and PA BTM17, the vacancy contents are d ¼ 0.097 and 0.103, respectively, which are consistent with our XRD refinements.…”
Section: -supporting
confidence: 88%
“…Our systematic TEM studies on Fe and Mn doped h-BaTiO 3 have revealed a structural incommensurate modulation rule, which is ascribed to the antiphase domain boundary (APB) structures. 18 Based on this, we report in this paper the magnetic properties of h-Ba(Ti 1Àx Mn x )O 3Àd (x ¼ 1/9, 1/6) samples. Associated with the thermal treatment effects and dielectric behavior analysis, we present experimental evidences on the origin of high-temperature FM in Mn-doped h-BaTiO 3 .…”
mentioning
confidence: 86%
See 1 more Smart Citation